PELAKSANAAN KEGIATAN POSYANDU LANSIA DI DESA PUDAK KABUPATEN MUARO JAMBI: Iin Indrawati - Iin Indrawati (Jurnal Psikologi Jambi, 2018)
INTRODUCTION Posyandu sejahtera 2 and 3 Pudak are Community self-help groups that manage the efforts of public health, especially the elderly. This posyandu has been established since 2010 but to date, the activities realized only the normal routine so less attractive to the elderly to come there. Visiting of elderly about 15 - 20 people of the total 600 people. METHOD This is a qualitative research, it was conducted at posyandu sejahtera 2 and 3 pudak villages by total informant 7 people. The main instrument is the researcher. The research was conducted during 6 months. RESULT The findings indicated that the implementation of posyandu activities in elderly are more enthused by elderly after the cadres obtain in training of Guidance on the implementation of Posyandu activities. The cadres indicated that they are more understanding of role and function as a cadre, determining of posyandu activities by 5 tables systems. Visiting the elderly increased by 2 times more than usual. It was built posyandu sejahtera 3 building with village funds. Head of the public health center and holders of the elderly program also have a commitment to Supports the elderly posyandu activities. CONCLUSION AND RECOMMENDATION The overall of general describing in pos yandu sejahtera 2 and 3 has been better that visible from cadre competence, increasing posyandu activity and increasing number of visiting elderly. For posyandu activities to continue well and continuously should be continued to realize refreshment knowledge cadre, socialization about the benefit of posyandu in elderly and also a commitment from society also village apparatus to extend special attention to the smoothness of posyandu activity. Keywords: Implementation of activities, elderly posyandu